From laboratory to in-situ 3D measurements of complex pollution states in the city: Introducing a general concept using compact multisensory assemblies on UAVs. (15th July 2022) - Lugassi, Rachel; Blank, Alexandra; Rogozovsky, Irina; Ohneiser, Kevin; Ansmann, Albert; Linzon, Yoav; Chudnovsky, Alexandra
Abstract: In the city, it is still a challenge to implement a mobile measurement device to accurately monitor its complex pollution state. Current research proposes new technological developments and many studies implement an Unmanned Aerial Vehicle (UAV)-based platforms. However, many questions arise on the representativeness of such measurements and on the UAV impact on data quality. Here, UAV is used to link between sparsely located ground monitoring sites and lidar station measuring pollution, the latter of which are at heights of typically >200 m. Information at intermediate heights are missing but needed for health studies and also for lidar validation algorithms. In this regard, we propose and demonstrate a UAV-based platform aimed at measuring meteorological and air quality parameters, namely, air temperature ( T air ), relative humidity (RH) and PM2.5 (Particulate matter pollution with a diameter of less than 2.5 μ m) on both compact and large UAV integrations. Each integration was separately investigated both numerically and experimentally in terms of the possible set of instruments used in the setup. In particular, custom-made meteorological shelters were constructed and tested in the laboratory under different propeller conditions. The best placement locations on the UAVs were verified using numerical airflow simulations employing real UAV geometries. Next, we compared between different sensors for T air on a diurnal cycle and deduced the best work time corresponding to minimal impact of the outside conditions (mainly due to direct sun exposure). The influence of propeller rotation on measured parameters has been studied in detail. In addition, a pilot field experiment was conducted in the urban domain using our platform and these measurements were compared to all available data sources. Our field experiment indicated a mixed local pollution layer up to 300 m. Finally, we suggest a practical guideline for carrying out field experiments employing both UAVs. We have also considered the fact that wide use of UAV technologies in crowded cities in the context presented in this paper is currently restricted by regulations and privacy that vary among different countries. Graphical abstract: Image 1 Highlights: We propose an Unmanned Aerial Vehicles (UAV)-based platform aimed at measuring meteorological and air quality parameters. The impact of different sensor configurations on a UAV-based platform performance was studied. Pre-flight inspection using numerical simulations and laboratory experiments was conducted. We characterize the city pollution state using UAVs, surface observations and lidar traces. We suggest practical guidelines for carrying out field experiments in the city employing UAVs.